Transfer of Aminonucleoside Nephrosis by Renal Transplantation - Hoyer, John R. (1972)
The pathogenesis of aminonucleoside of puromycin (PA) nephrotic syndrome in rats was studied using renal transplantation to separate systemic from renal factors. The nephrotic syndrome was transferred by transplantation of kidneys from rats with established proteinuria. Bilaterally nephrectomized normal rats receiving kidneys removed as early as 15 min after intravenous PA injection (100 mg/kg) of donors also developed proteinuria (602±125 mg/24 hr) and a nephrotic syndrome after the usual induction period of 4-7 days observed in this disease. Arterial perfusion of isolated kidneys with PA (50 mg/kg) followed by perfusion with isotonic saline 3 min later and then transplantation to normal bilaterally nephrectomized rats led to a nephrotic syndrome. Urine protein excretion was 494±42 mg on the 7th day after transplantation. In contrast, urine protein excretion after transplantation of normal kidneys to normal bilaterally nephrectomized rats was 40±20 mg on the 7th day. Exposure of a normal kidney to a nephrotic host environment by transplantation of a normal kidney to a unilaterally nephrectomized PA-injected rat did not transfer the disease to the normal kidney. After removal of the nephrotic kidney 11-13 days after transplantation, proteinuria of the donor kidney was normal (21±13 mg on day 15). These studies indicate that pathogenesis of aminonucleoside nephrosis involves programming of the kidney directly by PA within minutes after exposure although increased urinary protein excretion does not occur until several days later.